2019
DOI: 10.1097/md.0000000000014499
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation in atrial fibrillation and cognitive decline

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…In this sense, other studies carried out in hospitalized frail patients aged more than 75 years and nonagenarians found that anticoagulation was associated with low rates of stroke and bleeding, with a net benefit that was clearly superior to not being anticoagulated [30,31]. Moreover, anticoagulation has been associated with reduced cognitive impairment in patients with AF [32].…”
Section: Assessment Of the Risk Of Stroke And Bleeding In The Elderly Patientmentioning
confidence: 88%
“…In this sense, other studies carried out in hospitalized frail patients aged more than 75 years and nonagenarians found that anticoagulation was associated with low rates of stroke and bleeding, with a net benefit that was clearly superior to not being anticoagulated [30,31]. Moreover, anticoagulation has been associated with reduced cognitive impairment in patients with AF [32].…”
Section: Assessment Of the Risk Of Stroke And Bleeding In The Elderly Patientmentioning
confidence: 88%
“…From another study, the risk of cognitive decline appears to be stronger with earlier age of onset and longer duration of atrial fibrillation [54], but we did not have age of onset data to gauge whether participants in our cohorts had atrial fibrillation long enough to elicit statistically significant effects. We also did not have the data needed to consider the use of anticoagulants, which a recent meta-analysis found significantly reduced the effects of atrial fibrillation on cognitive decline [55].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the role of oral anticoagulants as first-line medication in the prevention of ischemic stroke in patients with AF [ 39 ], it is still debatable whether the risk of AF-related dementia can be significantly reduced by oral anticoagulation treatment [ 40 , 41 ]. Recent data suggest that the novel anticoagulants would be a better choice for the prevention of dementia than warfarin (a vitamin K antagonist) [ 42 , 43 ], probably due to a lower rate of intracerebral bleeding [ 43 ].…”
Section: Psychosocial Consequences Of Afmentioning
confidence: 99%